2019
DOI: 10.3390/nu11010209
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Dietary Protein and Fat Content on Intrahepatocellular and Intramyocellular Lipids during a 6-Day Hypercaloric, High Sucrose Diet: A Randomized Controlled Trial in Normal Weight Healthy Subjects

Abstract: Sucrose overfeeding increases intrahepatocellular (IHCL) and intramyocellular (IMCL) lipid concentrations in healthy subjects. We hypothesized that these effects would be modulated by diet protein/fat content. Twelve healthy men and women were studied on two occasions in a randomized, cross-over trial. On each occasion, they received a 3-day 12% protein weight maintenance diet (WM) followed by a 6-day hypercaloric high sucrose diet (150% energy requirements). On one occasion the hypercaloric diet contained 5% … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
11
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 42 publications
1
11
0
Order By: Relevance
“…Mot studies focusing on the association between fructose or saccharose overfeeding and liver fat steatosis (quantitated by MRI), have been performed in healthy or obese men [58,72,73,74,75,76,77,78,79]. Many of these studies have been positive [58,72,73,74,75,76,77,78,79]. For example, daily intake of one liter regular cola for 6 months in overweight subjects ( n = 10) was shown to associate with significant increases of liver fat measured by MRI, but without significant changes of BMI or total fat mass [80].…”
Section: Metabolic Effects Of Fructose Consumptionmentioning
confidence: 99%
“…Mot studies focusing on the association between fructose or saccharose overfeeding and liver fat steatosis (quantitated by MRI), have been performed in healthy or obese men [58,72,73,74,75,76,77,78,79]. Many of these studies have been positive [58,72,73,74,75,76,77,78,79]. For example, daily intake of one liter regular cola for 6 months in overweight subjects ( n = 10) was shown to associate with significant increases of liver fat measured by MRI, but without significant changes of BMI or total fat mass [80].…”
Section: Metabolic Effects Of Fructose Consumptionmentioning
confidence: 99%
“…The hypothesis that fructose may promote fatty liver disease is supported by available human data showing that consumption of a high fructose diet increases intrahepatic fat concentrations Surowska et al 2019). However, similar effects were also observed with short-term glucose (Johnston et al 2013; or fat (Sobrecases et al 2010) overfeeding trials, suggesting that rapid increases in intrahepatic fat concentrations may be more related to excess energy intake rather than fructose per se.…”
Section: Effects Of High Fructose Diets On Health and Health-related mentioning
confidence: 94%
“…A recent meta-analysis further indicated that this effect was observed with weight-maintenance diets as well as with hypercaloric high fructose diets (Ter Horst et al 2016). Some studies however reported that intramyocellular lipid concentrations were increased in healthy subjects overfed with sucrose (Surowska et al 2019) or in siblings of type 2 diabetes subjects overfed with fructose (Le et al 2009). It raises the concern that longer exposure to fructose may possibly impair muscle insulin sensitivity since increased intramyocellular lipid concentrations are thought to be associated with muscle insulin resistance (Gemmink et al 2017).…”
Section: Effects Of High Fructose Diets On Health and Health-related mentioning
confidence: 99%
See 2 more Smart Citations